Sosialisasi Teknik Feynman Untuk Meningkatkan Kualitas Belajar Siswi MTSS Al Fattah Kabupaten Sarolangun - Fitriah, Siti; Zulfa Agustin, Siti; Mestika Putra, Yoga; Amri, Ulil; Kartika Putri, Aprilia (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
The aim of this activity is to socialize learning techniques to improve the quality of learning of MTSS Al Fattah students in Sarolangun district. This activity is carried out to increase students' comprehension ability in understanding the lesson material. Therefore, we need a fairly effective technique that can be easily applied. The Feynman technique is a learning technique that is quite effective in overcoming this problem. The implementation of this service activity is carried out in two stages, namely the planning stage and the implementation stage. At the planning stage, the material that needs to be used as a learning object is determined. At the implementation stage, the lecture and question and answer method was applied. The lecture method is used to introduce the Feynman technique and how to apply it, and the question and answer method is used to determine the extent to which students understand the presentation and application of the Feynman technique in the learning process. The results of the assessment rubric showed that the majority of students can easily understand the lesson material after using the Feynman technique. It is known from the researchers' assessment that almost 72% of MTSS Al Fattah students can deliver material in front of the class very well. Apart from that, this service activity also received a positive response from the majority of MTSS Al Fattah students.